The feminist history reader - Morgan, Sue (Routledge, 2006)
The Feminist History Reader gathers together key articles, from some of the very best writers in the field, that have shaped the dynamic historiography of the past thirty years, and introduces students to the major shifts and turning points in this dialogue. The Reader is divided into four sections: early feminist historians' writings following the move from reclaiming women's past through to the development of gender history the interaction of feminist history with `the linguistic turn' and the challenges made by post-structuralism and the responses it provoked the work of lesbian historians and queer theorists in their challenge of the heterosexism of feminist history writing the work of black feminists and postcolonial critics/Third World scholars and how they have laid bare the ethnocentric and imperialist tendencies of feminist theory. Each reading has a comprehensive and clearly structured introduction with a guide to further reading, this wide-ranging guide to developments in feminist history is essential reading for all students of history.